1984
DOI: 10.1177/105381518400800209
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Group Instruction of Normally Developing and Autistic-like Children: The LEAP Curriculum Model

Abstract: This paper focuses on a description of an approach to individualize group instruction and an evaluation of preacademic/academic program effects for normally developing and autistic-like children, Essential features of the individualized group instruction procedure include: individualized curriculum for each class participant; frequent assessment of intervention impact; opportunities to revise curricular objectives; planning lessons that include objectives for each child; management of behavior in a group; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 7 publications
0
62
0
1
Order By: Relevance
“…The developmentally oriented approach is drawn from a developmental model of autism (Hoyson, Jamieson, & Strain, 1984;Rogers, Bennetto, McEvoy, & Pennington, 1996;Rogers & Pennington, 1991). Among the important components of the intervention are teaching imitation and developing awareness of social interactions and reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…The developmentally oriented approach is drawn from a developmental model of autism (Hoyson, Jamieson, & Strain, 1984;Rogers, Bennetto, McEvoy, & Pennington, 1996;Rogers & Pennington, 1991). Among the important components of the intervention are teaching imitation and developing awareness of social interactions and reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…A developmental/behavioral curriculum implemented in an integrated setting characterized the LEAP Program (Learning Experiences ...An Alternative Program for Preschoolers and Parents) carried out by Strain, Hoyson, and others [Hoyson et al, 1984]. The authors reported striking gains in six ''autisticlike'' children in language, intellectual levels, and behavior, using a pre-post design.…”
Section: Developmentally Based Modelsmentioning
confidence: 96%
“…For pre-2000 applied behavioranalytic research Gernsbacher did not review, see S. R. Anderson, Avery, DiPietro, Edwards, and Christian (1987), Fenske et al (1985), Handleman, Harris, Celierti, Lilleheht, and Tomchek (1991), Harris, Handleman, Gordon, Kristoff, and Fuentes (1991), Harris, Handleman, Kristoff, Bass, and Gordon (1990), Hoyson, Jamieson, and Strain (1984), Perry, Cohen, andDeCarlo (1995), andWeiss (1999). For literature reviews, see S. J.…”
Section: Misrepresenting Aba-eibi Research Imentioning
confidence: 99%